Ecospheres around binary stars - Deka, B. (Advances in Astronomy and Space Physics, 2011)
Scientific investigations concerning ecospheres of other stars are very important for understanding the posibilities of existence and evolution of extraterrestrial life. In several last years astronomers discovered hundreds of extrasolar planets. Identification of stars with ecospheres is the first step in selecting those planets which could be inhabited. Usually an ecosphere of a single star is considered but it may also exist in planetary systems with two suns. This possibility is very promising in search for life on other planets as more that 60 % of stars reside in binary or multiple systems.